MINERALOGY AND PETROGRAPHY OF TECHNOGENIC PARABASALTS FROM THE CHELYABINSK BROWN-COAL BASIN - Sharygin V.V.; Sokol E.V.; Nigmatulina E.N.; Lepezin G.G.; Kalugin V.M.; Frenkel' A.E. (My University, 1999)
Spontaneous burning in the largest spoil heaps of the Chelyabinsk coal basin led to high-temperature conditions (1000-1300°C). At these parameters, Fe-rich basic liquids resulted from the complete melting of a fine-crushed mixture of mudstones, calcareous clays, and siderites in zones of heaps with reduced gas annealing. Crystallization of these melts under dry reductive conditions (fO2 = 10-9 - 10-12, T = 1200-1000°C) at pressure close to 1 atm led to formation of parabasalts. These rocks differ greatly from all natural paralavas and terrestrial basalts in high Al2O3, FeO, CaO, P2O5 and low SiO2, MgO, Fe2O3, and Na2O contents. Plagioclase (An100-90), Mg-Fe-clinopyroxene (diopside, low- and high-alumina augite), and Mg-Fe-olivine (Fo60-15) are the main rock-forming minerals in the parabasalts. Fayalite (Fo10-3), Ti-magnetite, Al-spinel, leucite, hedenbergite, kirschsteinite, pyrrhotite, K-feldspar, fluorapatite, ilmenite, and glasses of two compositions (K-acid and Fe-basic) are minor phases. Low-Ca pyroxenes (orthopyroxene, pigeonite), tridimite and other SiO2 polymorphs, mullite, nepheline, chalcopyrite, pyrite, native iron, and shungite are found as accessories. Some minerals contain uncommon admixtures. Olivines contain up to 15 mole % larnite end-member, some olivines and kirschsteinites have P2O5 (up to 0.7 wt.%), apatite is rich in SiO2 (up to 6 wt.%), and K-feldspar is rich in BaO (up to 7.5 wt.%). In textural features, modal composition, mineral ratios, and order of mineral crystallization, the technogenic parabasalts correspond to shallow-depth basic rocks.